Parents of Young Children Select Picture Books Based on Information Not Found in Bibliographic Records - Warren, Ruby Muriel Lavallee (Evidence Based Library and Information Practice, 2016)
A Review of: Švab, K. & Žumer, M. (2015). The value of a library catalog for selecting children's picture books. Cataloging & Classification Quarterly, 53(7), 717-737. doi: 10.1080/01639374.2015.1044059 Objective – To determine how parents select picture books for their children, and which bibliographic data are important when selecting a specific version of a title with multiple interpretations. Design – Qualitative, with interviews and task-based controlled observational studies. Setting – A public library in Slovenia. Subjects – 36 parents of children between one and 6 years of age. Methods – The researchers recruited parents via convenience sampling in non-library, family-oriented locations (parks, playgrounds, beaches, and others). Participants were all interviewed regarding their methods of picture book selection and their use of library catalogues. Participants were then given six print bibliographic records for copies of Cinderella, available in libraries, and asked to select a book for their child based solely on these records. They were then presented with their selection and interviewed regarding their satisfaction with the book selected and their decision-making process. Finally, the researchers presented participants with all six physical copies of the book that had been represented by bibliographic records, and asked participants to select one of the books for their child. The researchers then interviewed participants regarding what information about the physical books should be included in records to assist in their decision-making. Main Results – Interviews indicated that the majority of participants did not use the library catalogue to select books for their children, and did not expect librarian or bookseller assistance. Many participants expressed browsing behaviours as the primary method of obtaining new picture books, and the strongest criteria for picture book selection among participants were subjective judgements regarding illustrations and content. However, when asked to use just bibliographic records to select a version of Cinderella, most participants selected a title using the author field and year of publication. 67% of participants were then dissatisfied with their selection due to factors such as illustration type, font size, and length or complexity of text. When choosing from all six physical copies, most participants disregarded condition issues and selected the oldest edition, favouring its colourful illustrations and textual length. Conclusions – The authors concluded that illustrations and book content were more important than other factors, including physical condition of the book, and that existing library catalogues were inadequate for picture book selection. They suggested that library catalogues should include further information about picture books, such as cover images, sample pages, book condition, and information about the type of text (whether it is the original, abridged, or an adaptation). They supported this by explaining that participants used the bibliographic fields already available (author, year of publication) to try and guess at what they actually considered important (the aforementioned suggested fields). In addition, they believed that their study indicated that users require a transparent and systematic way to review and compare versions of a given text. Finally, the authors recommended further study using enriched bibliographic records and additional data collection methods, such as focus groups and questionnaires. The authors have several further studies in this area planned.